2006
DOI: 10.1103/physrevb.74.174418
|View full text |Cite
|
Sign up to set email alerts
|

Competition between intragranular and intergranular tunneling magnetoresistance in polycrystallineSr2FeMoO6

Abstract: Polycrystalline Sr 2 FeMoO 6 ͑SFMO͒ samples with various grain sizes and densities of Fe/ Mo disorder defects were synthesized from sol-gel-derived precursors by means of a sample-encapsulation technique. The samples with perfect Fe/ Mo ordering exhibited metallic transport behavior and a large magnetoresistance ͑MR͒ effect, whereas the samples with a high-disorder density and small grain size showed a metal-insulator transition and lower MR values. It is suggested that a competition between intragranular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Indeed, temperature dependent resistivity measurements on the AD 40% sample showed a minimum around 40 K, i.e., the resistivity increased with decreasing temperature below 40 K, while on the AD 10% one there was no minimum till the lowest measured temperature (20 K). The observations are consistent with previous reports of transport measurements on SFMO having various degrees of disorder [16,19] and on SFMO with high Fe/Mo ordering [13,20]. For a fixed degree of disorder, the intensity at E F increased with temperature as shown in Fig.…”
supporting
confidence: 92%
“…Indeed, temperature dependent resistivity measurements on the AD 40% sample showed a minimum around 40 K, i.e., the resistivity increased with decreasing temperature below 40 K, while on the AD 10% one there was no minimum till the lowest measured temperature (20 K). The observations are consistent with previous reports of transport measurements on SFMO having various degrees of disorder [16,19] and on SFMO with high Fe/Mo ordering [13,20]. For a fixed degree of disorder, the intensity at E F increased with temperature as shown in Fig.…”
supporting
confidence: 92%
“…Huang et al [13] observed coexistence of inter-granular and intra-granular tunneling magneto-resistances and the competition between two determines the magneto-transport properties of these systems. However, Sarma et al [4] proved that major part of magneto-resistance in these double perovskite systems come from intergrain tunneling (tunneling through grain boundaries), and not due to barrier created through ASD defects.…”
Section: Article In Pressmentioning
confidence: 98%
“…However, it has thus far been difficult to prepare Sr 2 FeMoO 6 samples with this high magnetic moment with most of the experimental moments ͑2.2-3.9 B per formula unit or /f.u.͒ reported to date being less than this expected value. [3][4][5][6] The origin of LFMR and low saturation magnetic moment were commonly attributed to two main types of defects, antisite defects and grain boundaries, and they have attracted much attention from many groups in the past decade. [3][4][5][6][7][8][9] Defined as the misplacement of Fe ions with Mo ions, antisite defects have been shown to affect the transport and magnetic properties of Sr 2 FeMoO 6 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The origin of LFMR and low saturation magnetic moment were commonly attributed to two main types of defects, antisite defects and grain boundaries, and they have attracted much attention from many groups in the past decade. [3][4][5][6][7][8][9] Defined as the misplacement of Fe ions with Mo ions, antisite defects have been shown to affect the transport and magnetic properties of Sr 2 FeMoO 6 . 8,10-12 Garcia-Hernandez et al 8 reported that disorder at the Fe and Mo sites was responsible for the linear dependence of the saturation magnetization on the LFMR in bulk Sr 2 FeMoO 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation